Association of Prescription With Body Composition and Patient Outcomes in Incident Peritoneal Dialysis Patients - Verger, Christian; Ronco, Claudio; Van Biesen, Wim; Heaf, James; Vrtovsnik, François; Vera Rivera, Manel; Puide, Ilze; Azar, Raymond; Gauly, Adelheid; Atiye, Saynab; De los Ríos, Tatiana (Frontiers in Medicine, 2021)
Objective The nutritional status of peritoneal dialysis (PD) patients is influenced by patient and disease related factors and lifestyle. This analysis evaluated the association of PD prescription with body composition and patient outcomes in the prospective incident IPOD-PD patient cohort. Design and Methods In this observational, international cohort study with longitudinal follow-up of 1054 incident PD patients, the association of PD prescription with body composition was analyzed by linear mixed models, and the association of body composition with death and change to HD by means of a competing risk analysis combined with a spline analysis. Results Age, time on PD, and the use of hypertonic and polyglucose solutions were significantly associated with a decrease in lean tissue index (LTI) and an increase in fat tissue index (FTI) over time. Competing risk analysis revealed a U-shaped association of BMI with the subdistributional hazard ratio for risk of death. High LTI was associated with a lower subdistributional hazard ratio, whereas low LTI was associated with an elevated subdistributional hazard ratio when compared to the median LTI as a reference. High FTI was associated with a higher subdistributional hazard ratio when compared to the median as a reference. Subdistributional hazard ratio for risk of change to HD was not associated with any of the body composition parameters. Use of polyglucose or hypertonic PD solutions were predictive of an increased probability of change to HD, and use of biocompatible solutions were predictive of a decreased probability of change to HD. Conclusion Body composition is associated with non-modifiable patient-specific and modifiable treatment-related factors. The association between lean tissue and fat tissue mass and death and change to HD in patients on PD suggests developing interventions and patient counselling to improve nutritional markers and, ultimately, patient outcomes.